2005
DOI: 10.3354/meps301109
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition of photosynthesis is reduced by water flow in the reef-building coral Acropora digitifera

Abstract: While photosynthesis of symbiotic algae is essential for reef-building corals, excess irradiance inhibits photosynthesis through photoinhibition, which can lead to coral bleaching under elevated temperature conditions. Here we show that water flow reduces photoinhibition of in hospite endosymbionts in the coral Acropora digitifera. Diurnal monitoring of chlorophyll fluorescence, under 2 different flow regimes (< 3 and 20 cm s -1 flow rates) in an outdoor aquarium, showed reduced photoinhibition, but only under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 52 publications
4
52
0
Order By: Relevance
“…This same trend was also observed after a thermal stress event in 2010 [51]. Increased heat and high irradiance can act synergistically to induce coral bleaching [2,[66][67][68][69][70]. Both studies attributed the relative resilience of the bay communities to thermal resistance in the animal and symbionts, and reduced irradiance due to high light attenuation in bay water compared to the clear oceanic waters found at fringe and patch reef sites.…”
Section: Spectral Response To Heatingsupporting
confidence: 51%
“…This same trend was also observed after a thermal stress event in 2010 [51]. Increased heat and high irradiance can act synergistically to induce coral bleaching [2,[66][67][68][69][70]. Both studies attributed the relative resilience of the bay communities to thermal resistance in the animal and symbionts, and reduced irradiance due to high light attenuation in bay water compared to the clear oceanic waters found at fringe and patch reef sites.…”
Section: Spectral Response To Heatingsupporting
confidence: 51%
“…Several authors have reported positive effects of water flow on photosynthesis in corals (Dennison and Barnes, 1988;Lesser et al, 1994;Nakamura et al, 2005;Finelli et al, 2006;Mass et al, 2010;Schutter et al, 2011). In a flume experiment with Galaxea fascicularis, Schutter et al (2011) found an instantaneous increase in photosynthesis upon an increase in flow velocity from 5 to 20 cm s −1 , which supports the idea that the effects of flow on photosynthesis are related to an improved exchange of dissolved gases.…”
Section: Introductionsupporting
confidence: 69%
“…In a flume experiment with Galaxea fascicularis, Schutter et al (2011) found an instantaneous increase in photosynthesis upon an increase in flow velocity from 5 to 20 cm s −1 , which supports the idea that the effects of flow on photosynthesis are related to an improved exchange of dissolved gases. However, it remains unclear whether this flow effect relates to a higher influx of carbon dioxide into the coral tissue (Dennison and Barnes, 1988;Lesser et al, 1994) or to a higher efflux of oxygen out of the coral tissue (Nakamura et al, 2005;Finelli et al, 2006;Mass et al, 2010;Schutter et al, 2011). Mass et al (2010) demonstrated that the onset of flow led to a decrease of oxygen supersaturation from 500% to 200% inside illuminated tissue of the scleractinian coral Favia veroni.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the interrelatedness of temperature and light has reciprocal effects, whereby the increase in temperature under high light conditions will be perceived by the symbionts as an increase in light stress, and vice versa (Iglesias-Prieto et al 2004;Takahashi et al 2004;Nakamura et al 2005). Figure 4 shows the considerably reduced scalar irradiance in Nikko Bay, compared with that at the Outer Eastern Reef site where the attenuation is more characteristic of a clear oceanic water type (Kirk 1994).…”
Section: Palau's Reefs In Contextmentioning
confidence: 98%